Sociopsychological determinants of functional foods consumption in China: based on the theory of the planned behavior expansion model - Huimin Jia; Shuang Liu (Frontiers in Nutrition)
This study investigates the determinants of Chinese consumers’ purchase intentions and behavior toward functional foods, incorporating health consciousness and trust into the theory of planned behavior (TPB) as a conceptual framework. An online quota-sample survey was conducted on 1,011 Chinese consumers. Structural equation modeling was used to test the proposed hypotheses. Three main findings were drawn based on the analysis: (1) Health consciousness significantly improved consumers’ attitudes towards functional foods (β = 0.921, p < 0.001); (2) Consumption intention was predominantly predicted by attitude (β = 0.751, p < 0.001), followed by perceived behavioral control (β = 0.148, p < 0.05) and trust (β = 0.115, p < 0.001). (3) Contrary to theoretical expectations, the positive influence of subjective norm (β = 0.222, p > 0.05) on purchase intention is not significant, and the purchase intention did not significantly influence behavior. Notably, perceived behavioral control (β = 0.841, p < 0.001) emerged as the strongest direct predictor of consumption behavior. This research empirically validates the explanatory power of the expanded Theory of Planned Behavior (TPB) in the context of functional food consumption. The results establish a more detailed conceptual framework for understanding consumption mechanisms, while providing evidence-based strategies for market development and public health interventions.